Mouse CD146+ muscle interstitial progenitor cells differ from satellite cells and present myogenic potential - Mierzejewski, Bartosz (Stem Cell Res Ther, 2020)
BACKGROUND: The skeletal muscle regeneration relays on the satellite cells which are stem cells located between basal lamina and plasmalemma of muscle fiber. In the injured muscles, the satellite cells become activated, start to proliferate, and then differentiate into myoblasts, which fuse to form myotubes and finally myofibers. The satellite cells play the crucial role in the regeneration; however, other cells present in the muscle could also support this process. In the present study, we focused on one population of such cells, i.e., muscle interstitial progenitor cells. METHODS: We used the CD146 marker to identify the population of mouse muscle interstitial cells. We analyzed the expression of selected markers, as well as clonogenic, myogenic, adipogenic, and chondrogenic potential in vitro. Simultaneously, we analyzed satellite cell-derived myoblasts and bone marrow-derived mesenchymal stem/stromal cells that allowed us to pinpoint the differences between these cell populations. Moreover, we isolated CD146+ cells and performed heterotopic transplantations to follow their in vivo differentiation. RESULTS: Mouse muscle CD146+ interstitial progenitor cells expressed nestin and NG2 but not PAX7. These cells presented clonogenic and myogenic potential both in vitro and in vivo. CD146+ cells fused also with myoblasts in co-cultures in vitro. However, they were not able to differentiate to chondro- or adipocytes in vitro. Moreover, CD146+ cells followed myogenic differentiation in vivo after heterotopic transplantation. CONCLUSION: Mouse CD146+ cells represent the population of mouse muscle interstitial progenitors that differ from satellite cell-derived myoblasts and have clonogenic and myogenic properties.